Stevens-Johnson Syndrome Following Non-steroidal Anti-inflammatory Drugs: A Real-World Analysis of Post-marketing Surveillance Data - Shao, Qi-hui; Yin, Xue-dong; Zeng, Na; Zhou, Zhi-xuan; Mao, Xin-yu; Zhu, Yan; Zhao, Bin; Li, Zhi-ling (Frontiers in Pediatrics, 2022)
Background The Stevens-Johnson syndrome (SJS) is a severe skin reaction to non-steroidal anti-inflammatory drugs (NSAIDs), and can even be life-threatening. However, there are still few real-world studies to compare the specific differences in the adverse effects of skin and mucosal invasion. Methods Disproportionality analysis and Bayesian analysis were devoted to data-mining of the suspected SJS after using NSAIDs based on the FDA’s Adverse Event Reporting System (FAERS) from January 2004 to March 2021. The times to onset, fatality, and hospitalization rates of antipyretic analgesic-associated SJS were also investigated. Results A total of 1868 reports of SJS adverse events were identified with NSAIDs. Among 5 NSAIDs monotherapies we studied (acetaminophen, ibuprofen, aspirin, diclofenac and celecoxib), ibuprofen had the highest association with SJS based on the highest reporting odds ratio (ROR = 7.06, 95% two-sided CI = 6.59-7.56), proportional reporting ratio (PRR = 6.98, χ2 = 4201.14) and empirical Bayes geometric mean (EBGM = 6.78, 95% one-sided CI = 6.40). However, ibuprofen-associated SJS had the lowest fatality rate (6.87%, p < 0.0001) and the highest hospitalization rate (79.27%, p < 0.0001). Celecoxib-associated SJS had the latest time to onset (317.56 days, p < 0.0001). Diclofenac-associated SJS cases appeared to be associated with the highest risk of death (25.00%, p<0.0001). Conclusions The analysis of FAERS data provides a more accurate profile of the incidence and prognosis of SJS after NSAIDs treatment, enabling continued surveillance and timely intervention in patients at risk of SJS following these NSAIDs.